Mesenchymal Stem Cell Secretion of SDF-1α Modulates Endothelial Function in Dilated Cardiomyopathy - Premer, Courtney; Wanschel, Amarylis; Porras, Valeria; Balkan, Wayne; Legendre-Hyldig, Tatiana; Saltzman, Russell G.; Dong, Chunming; Schulman, Ivonne Hernandez; Hare, Joshua M. (Frontiers in Physiology, 2019)
Background: Endothelial dysfunction contributes to the pathophysiology of dilated cardiomyopathy (DCM). Allogeneic but not autologous mesenchymal stem cells (MSCs) improve endothelial function in DCM patients. We hypothesized that these effects are modulated by release of stromal derived factor-1α (SDF-1α). Methods: Plasma TNFα and endothelial progenitor cell-colony forming units (EPC-CFUs) were assessed at baseline and 3-months post-injection in a subset of POSEIDON-DCM patients that received autologous (n=11) or allogeneic (n=10) MSCs. SDF-1α secretion by MSCs, endothelial cell (EC) TNFα mRNA expression and levels of reactive oxygen species (ROS) in response to SDF-1α were measured in vitro. Results: As previously shown, DCM patients (n=21) had reduced EPC-CFUs at baseline (3±3), which were restored to normal by allogeneic MSCs 3-months post-treatment (Δ10±4). DCM patients had elevated baseline plasma TNFα (n=15, 22±9.4pg/mL). Allogeneic MSCs (n=8) decreased, and autologous MSCs (n=7) increased, plasma TNFα (-7.1±3.1 vs. 22.2±17.1pg/mL respectively; P=0.0005). In culture, autologous MSCs (n=11) secreted higher levels of SDF-1α than allogeneic MSCs (n=6) [76.0 (63.7, 100.9) vs. 22.8 (7.2, 43.5) pg/mL, P=0.0002]. SDF-1α and plasma TNFα negatively correlated with EPC-CFUs in both treatment groups (R=-0.7, P=0.0004). ECs treated with 20ng SDF-1α expressed lower levels of TNFα mRNA than cells treated with 100ng (0.7±0.2 vs. 2.1±0.3, P=0.0008). SDF-1α at low but not high concentration inhibited the generation of ROS. Conclusions: MSC secretion of SDF-1α inversely correlates with EPC-CFU production in DCM patients and therefore may be a modulator of MSC therapeutic effect in this clinical setting. Clinical Trial Registration: NCT01392625; https://clinicaltrials.gov/ct2/show/NCT01392625